Infection control: Knowledge and compliance among Saudi undergraduate dental students - Al-Maweri, Sadeq Ali; Tarakji, Bassel; Shugaa-Addin, Bassam; Al-Shamiri, Hashem M.; Alaizari, Nader Ahmed; AlMasri, Ousamah (German Medical Science GMS Publishing House, 2015)
Objective: This study aimed to assess the level of knowledge, attitudes, and practices regarding infection control procedures among undergraduate dental students. Methods: This was a questionnaire-based cross-sectional survey. A self-administered questionnaire consisting of questions on students' vaccination status as well as knowledge and attitudes regarding infection control was sent to 600 undergraduate dental students in the fourth, fifth, and sixth year of the Al-Farabi College for Dentistry and Nursing, Riyadh, Saudi Arabia. The collected data were analyzed using SPSS software. The significance level was set at <0.05. Results: The response rate was 85% (512 out of 600). While the vast majority of students (90%) had been vaccinated against hepatitis, only 37.4% have been assessed for anti-HBs. A total of 98.8% and 90.8% reported always wearing gloves and masks, respectively, during dental procedures. The use of protective eyewear was reported by only 29.2%. A significantly higher proportion of sixth-year students showed a positive attitude toward the treatment of patients with infectious diseases than other students of lower academic years. Approximately one-third of students reported having one or more occupational injuries while treating their patients. Conclusion: Although the students had good knowledge and attitudes regarding infection control, the compliance and practice levels regarding the same were low. Such findings highlight the necessity of continued infection-control education of Saudi dental students.